2012
DOI: 10.1111/pan.12074
|View full text |Cite
|
Sign up to set email alerts
|

Absorption characteristics of epidural levobupivacaine with adrenaline and clonidine in children

Abstract: The addition of adrenaline decreases the rate of levobupivacaine systemic absorption, reducing peak concentration by half. Levobupivacaine concentrations with adrenaline adjuvant were reduced compared to plain levobupivacaine for up to 3.5 hours. Clonidine as an adjuvant results in faster systemic absorption of levobupivacaine and similar concentration time profile to levobupivacaine alone. Adding adrenaline with clonidine does not alter the concentration profile observed with adrenaline alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 47 publications
2
18
1
Order By: Relevance
“…In contrast with the studies cited above [15,25,26], the time-course of plasma lidocaine concentration had quasi-straight absorption phase slopes with abrupt slope changes (Fig 7), a shape that resembles a short stepwise i.v. infusion and is suggestive of at least two zero-order absorption processes [29].…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…In contrast with the studies cited above [15,25,26], the time-course of plasma lidocaine concentration had quasi-straight absorption phase slopes with abrupt slope changes (Fig 7), a shape that resembles a short stepwise i.v. infusion and is suggestive of at least two zero-order absorption processes [29].…”
Section: Discussioncontrasting
confidence: 77%
“…One possible modification is to replace the dual first-order, asynchronous absorption rates with two zero-order, time-constrained absorption rates, a strategy tried for the PK modeling of the epidural block with levobupivacaine [15]. Although these investigators found that the goodness-of-fit of this alternative model was lower than their original model, other authors have found it useful to fit the i.m.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clonidine combined with levobupivacaine has a faster onset of sensory and motor block which was in accordance with Milligan KR et al 12 , Gupta S et al 13 and Jain A et al 14 Clonidine being a lipophilic drug is rapidly absorbed into the spinal compartment and blocks the conduction of C and Aδ fibres. 15 Chalkiadis DS et al 16 in their study demonstrated the absorption characteristics of epidural levobupivacaine with clonidine and adrenaline via caudal epidural route and showed that clonidine mixed with levobupivacaine had a faster absorption compared to adrenaline mixed with levobupivacaine.…”
Section: Discussionmentioning
confidence: 99%